Complete atrial-specific knockout of sodium-calcium exchange eliminates sinoatrial node pacemaker activity. - Sabine Groenke; Eric D Larson; Sarah Alber; Rui Zhang; Scott T Lamp; Xiaoyan Ren; Haruko Nakano; Maria C Jordan; Hrayr S Karagueuzian; Kenneth P Roos; Atsushi Nakano; Catherine Proenza; et al. (PLoS ONE)
The origin of sinoatrial node (SAN) pacemaker activity in the heart is controversial. The leading candidates are diastolic depolarization by "funny" current (If) through HCN4 channels (the "Membrane Clock" hypothesis), depolarization by cardiac Na-Ca exchange (NCX1) in response to intracellular Ca cycling (the "Calcium Clock" hypothesis), and a combination of the two ("Coupled Clock"). To address this controversy, we used Cre/loxP technology to generate atrial-specific NCX1 KO mice. NCX1 protein was undetectable in KO atrial tissue, including the SAN. Surface ECG and intracardiac electrograms showed no atrial depolarization and a slow junctional escape rhythm in KO that responded appropriately to β-adrenergic and muscarinic stimulation. Although KO atria were quiescent they could be stimulated by external pacing suggesting that electrical coupling between cells remained intact. Despite normal electrophysiological properties of If in isolated patch clamped KO SAN cells, pacemaker activity was absent. Recurring Ca sparks were present in all KO SAN cells, suggesting that Ca cycling persists but is uncoupled from the sarcolemma. We conclude that NCX1 is required for normal pacemaker activity in murine SAN.